Standardizing Immunohistochemistry: A New Reference Control for Detecting Staining Problems. (September 2015) - Sompuram, Seshi R.; Vani, Kodela; Tracey, Brian; Kamstock, Debra A.; Bogen, Steven A.
A new standardized immunohistochemistry (IHC) control for breast cancer testing comprises formalin-fixed human epidermal growth factor receptor 2, estrogen receptor, or progesterone receptor peptide antigens covalently attached to 8-µm glass beads. The antigen-coated beads are suspended in a liquid matrix that hardens upon pipetting onto a glass microscope slide. The antigen-coated beads remain in place through deparaffinization, antigen retrieval, and immunostaining. The intensity of the beads' stain provides feedback regarding the efficacy of both antigen retrieval and immunostaining. As a first report, we tested the sensitivity and specificity of the new IHC controls ("IHControls"). To evaluate sensitivity, various staining problems were simulated. IHControls detected primary and secondary reagent degradation similarly to tissue controls. This first group of IHControls behaved similarly to tissue controls expressing high concentrations of the antigen. The IHControls were also able to detect aberrations in antigen retrieval, as simulated by sub-optimal times or temperatures. Specificity testing revealed that each antigen-coated bead was specific for its cognate IHC test antibody. The data support the conclusion that, like tissue controls, IHControls are capable of verifying the analytic components of an immunohistochemical stain. Unlike tissue controls, IHControls are prepared in large bulk lots, fostering day-to-day reproducibility that can be standardized across laboratories.